Oxigenoterapia y su influencia en infecciones respiratorias en adultos mayores que asisten al área de observación Hospital Luis Vernaza Guayaquil – Guayas octubre 2018 - abril 2019 - Murillo Peñafiel, Haylis Yailing (2019)
This research project is based on diseases of respiratory insufficiency. They are very frequent conditions. They constitute an important cause of morbidity and mortality in all ages. Where the smoking medium influences the development of these types of pathologies. It is one of the main causes of the development of (IR), where it is estimated among 50% of active smokers. The objective of this research is to apply strategies with adequate procedures to improve the respiratory infections diseases in older adults who attend the Luis Vernaza Guayaquil Hospital observation area in the 2018-2019 semester. With the purpose of improving the quality of life of patients with (IR). As a methodology used in this analytical, deductive and exploratory study of the study and as a deductive - induce research method, where a sample of 100 people was used, where 90 people suffered from a respiratory infection disease. Obtaining as a result of the survey applicable in the Luis Vernaza Hospital of 50%, they are active smokers and it has developed in diseases of respiratory infections by tobacco, in which 93% is the main cause of these pathologies. It is recommended to deepen the information collected from patients for a more effective treatment of oxygen therapy. It is proposed as a proposal to implement preventive measures and to inform family members of the proper determination regarding oxygen therapy and its incidence in the development of respiratory infections. Treat pulmonary hypertension and reduce respiratory and myocardial work. In acute situations, its usefulness is widely accepted and in chronic situations it has spread significantly.